Surgical stabilization of rib fracture patients versus nonoperative controls treated by a multidisciplinary team in a single institution - Frank Bauer; Susan Haag; Kaveh Najafi; Brian Miller; John Kepros (Heliyon, 2023)
Introduction: Despite promising evidence, surgical stabilization of rib fractures (SSRF) is not ubiquitously offered in all trauma centers. Some centers struggle with patient selection while some struggle due to surgeon comfort with the technique. To address this issue, our trauma center developed a multidisciplinary SSRF approach between orthopedic and trauma surgery. Methods: This retrospective study compared 43 patients who underwent SSRF at a level 1 trauma center with 43 nonoperatively managed controls. Our study Indications were flail chest with >3 segments; non-flail with severe, bi-cortical displacement of >3 contiguous segments. Main outcome measures included mortality, ICU duration, hospital stay LOS, rates of ventilator-associated pneumonia (VAP) and ventilator days. Results: Results of SSRF included decreases in mortality (2% vs 16.3%; p = 0.03) and in ICU duration. Patients with SSRF had a significantly shorter duration in the ICU than the nonoperative group (8.72 vs 14 days; p = 0.013) but a similar hospital duration (LOS mean, 12.81 vs 15.2; p = 0.29). Less patients in the SSRF group developed VAP but the difference was not significant (2% vs 14%, p = 0.055). Discussion: SSRF patient outcomes supported prior evidence. The tandem approach had benefits as surgeons were able to leverage skills and expertise, increase collaboration between services, and complete more difficult reconstructions. Our experience may serve as a model for trauma centers interested in starting a new program or enhancing current service offerings.